(3LhGgQ GdYbOjf aj aVd GdTQajf TQa GdYde GdLdi hGdfSH GdYdis - (3Ydj Hf YHO Gddg GdMSjfj GdSeghOj GdTGaYjs ((3CMeO Hf YHO GdMajX s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CYR ChdjGA CYdGe GdOjf CeG HYO aEf Gddg JYGdi bO ENJU YHGOg Cgd GdYde GdSfi hCgd GdHjJ GdfHhi HNUjUG GdTQa GdYdi hMHGge QajY GdOQLGJ s
(3BNQgG (B:s
(3aeMGSf GdBd GdcQGe cKjQI dGjMUgG CMO Shi GdefGf hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B614s
Keywords: (3GdJGQjNs